The internal context of bilingual processing - Truscott, John (College teacher) (Bilingual processing and acquisition ;, 2019)
"This book offers a broad-based account of bilingual processing, drawing on research findings and current thinking from various domains across cognitive science. The theoretical approach adopted is the Modular Cognition Framework in which language processing is characterized as an interaction between dedicated linguistic systems and the other modules of the human mind. The latter provide the 'internal context' of bilingual processing. This internal context involves goals, value, emotion, self, and representations of the external context. The book combines all these elements into a coherent picture of the bilingual's internal context and the way it shapes processing. It then shows how some central concepts in cognitive science and bilingualism fit in with - and follow from - this view. These concepts include working memory, consciousness, attention, effort, codeswitching, and the possible cognitive benefits of being bilingual. The book should be of interest to professionals in the field as well as postgraduate students and advanced undergraduates"--